Pengaruh Word Of Mouth Communication dan Kualitas Pelayanan Terhadap Keputusan Pembelian - Ompon Lastiur Sianipar; Eka Pratiwi Septania Parapat; Eko Deswin Miechaels Siringo-ringo (SEKOLAH TINGGI AKUNTANSI DAN MANAJEMEN INDONESIA (STAMI), 2022)
This study aims to determine the effect of word of mouth communication and service quality on customer satisfaction partially and simultaneously. This type of research uses associative with a quantitative approach. The research sample was 348 people. The analytical method used in this research is multiple linear regression analysis. Word of mouth communication has five statement indicators by producing a reliability test value of 73%, and the majority of respondents agree with the statement. The results obtained that partially word of mouth communication has a positive and significant effect on purchasing decisions, with a tcount value of 11,546 > a ttable value of 1,967 or a significance value of 0.000 <α (0.05). The quality of service has five indicators of statements by producing a reliability test value of 77%, and the majority of respondents agree with the statement. The results showed that partially service quality had a positive and significant effect on purchasing decisions, with the tcount value of 12,850 > ttable value of 1,967 or a significance value of 0.000 < (0.05). Purchasing decisions have five statement indicators by producing a reliability test value of 72.1%, and the majority of respondents agree with the statement. Simultaneously word of mouth communication and service quality have a positive and significant effect on purchasing decisions, with the Fcount value of 377,114 > Ftable value of 3,022 or a significance value of 0.000 < (0.05).